DIGITAL RECONSTRUCTION OF SINGOSARI TEMPLE USING STRUCTURE FROM MOTION METHODS - Hidayat, Husnul; Cahyono, Agung Budi (Departemen Teknik Geomatika ITS, 2016)
Singosari temple is one of cultural heritage building in Indonesia. This temple is located in Singosari District, Malang Regency, East Java, about 9 kilometers from Malang City to Surabaya. This temple is predicted to be built in 1300s and has been restorated by Dutch colonial government in 1934-1937. Today, there are some incomplete parts at the temple. Due to its history and recent condition, the documentation of this building becomes so important not only for archaeological purposes, but also education and tourism. This research aims to make documentations about this temple by digital 3D model reconstruction. The main data which used in this research are 39 terrestrial images of the temple which were taken with digital camera. Then, the 3D model was reconstructed using Structure from Motion algorithm. In order to make a 3D model with correct dimension, position, and orientation, the georeferencing process was done with aid from control points which have known absolute coordinate obtained from terrestrial surveying. To check the geometric accuracy of 3D model, the accuracy test was carried out by comparing the coordinates from 3D model and length measurement with corresponding real values from terrestrial surveying. The result shows that with only terrestrial images the generated 3D model was still incomplete. Visually the walls can be modeled well. But the top and floor can’t be modeled due to lack coverage from the top. In terms of geometric accuracy, the mean 3D positional error is 0.068 m. And the mean of error in length measurement is 0.057 m.